Local economic development in the context of mine downscaling: the case of Orkney, North West Province, South Africa - Nthatisi, Tlhopane Lebogang (University of the Free State, 2022)
The discovery of minerals such as gold, diamond, copper, etc. in the 1800s has set the development trajectory of South Africa on an upswing. The dawn of mining as an economic activity resulted in mass migration to areas with rich mineral deposits, which was followed by the establishment of settlements and industrialisation of the sector. Over the years, the mining sector has firmly entrenched itself as the backbone of the South African economy. The mining industry is responsible for the creation of mass job and economic opportunities across the various towns and cities that it operates in. Tied to economic opportunities, mining played a significant part in the social upliftment of communities by providing social housing, skill and empowerment programmes, recreational facilities, etc. At the height of its existence, the mining industry was a darling to the community, the government and civil society to a point that it was a prominent figure shaping the development trajectory of the state. However, as the mineral deposits and reserves started to decrease and downscaling of mining activities across various towns and cities was evident, the relationship between the mining sector and the general populace of South Africa deteriorated. This was a result of massive job losses, the emergence of social ills such as poverty, crime, and substance abuse due to the withdrawal of mine operations and related declines in economic opportunities. This study aims to explore the local economic development interventions that the various stakeholders in the Greater Orkney area have adopted to resuscitate its local economy in light of continuing mine closures. This will look at programmes, plans, actions and roles that the various stakeholders have implemented to curb the negative social and economic impacts of mine closures. The research findings will inform policy discussions and programmes relating to local economic development to mitigate the effects of mine closures.
Dissertation (MDS (Development Studies))--University of the Free State, 2022